On-chip high-definition bioprinting of microvascular structures. (17th December 2020) - Dobos, Agnes; Gantner, Franziska; Markovic, Marica; Van Hoorick, Jasper; Tytgat, Liesbeth; Van Vlierberghe, Sandra; Ovsianikov, Aleksandr
Abstract: 'Organ-on-chip' devices which integrate three-dimensional (3D) cell culture techniques with microfluidic approaches have the capacity to overcome the limitations of classical 2D platforms. Although several different strategies have been developed to improve the angiogenesis within hydrogels, one of the main challenges in tissue engineering remains the lack of vascularization in the fabricated 3D models. The present work focuses on the high-definition (HD) bioprinting of microvascular structures directly on-chip using two-photon polymerization (2PP). 2PP is a nonlinear process, where the near-infrared laser irradiation will only lead to the polymerization of a very small volume pixel (voxel), allowing the fabrication of channels in the microvascular range (10–30 µ m in diameter). Additionally, 2PP not only enables the fabrication of sub-micrometer resolution scaffolds but also allows the direct embedding of cells within the produced structure. The accuracy of the 2PP printing parameters were optimized in order to achieve high-throughput and HD production of microfluidic vessel-on-chip platforms. The spherical aberrations stemming from the refractive index mismatch and the focusing depth inside the sample were simulated and the effect of the voxel compensation as well as different printing modes were demonstrated. Different layer spacings and their dependency on the applied laser power were compared both in terms of accuracy and required printing time resulting in a 10-fold decrease in structuring time while yielding well-defined channels of small diameters. Finally, the capacity of 2PP to create vascular structures within a microfluidic chip was tested with two different settings, by direct embedding of a co-culture of endothelial- and supporting cells during the printing process and by creating a supporting, cell-containing vascular scaffold barrier where the endothelial cell spheroids can be seeded afterwards. The functionality of the formed vessels was demonstrated with immunostaining of vascular endothelial cadherin (VE-Cadherin) endothelial adhesion molecules in both static and perfused culture.